2019
DOI: 10.1111/cmi.13121
|View full text |Cite
|
Sign up to set email alerts
|

Vital role forPlasmodium bergheiKinesin8B in axoneme assembly during male gamete formation and mosquito transmission

Abstract: Sexual development is an essential phase in the Plasmodium life cycle, where male gametogenesis is an unusual and extraordinarily rapid process. It produces 8 haploid motile microgametes, from a microgametocyte within 15 minutes. Its unique achievement lies in linking the assembly of 8 axonemes in the cytoplasm to the three rounds of intranuclear genome replication, forming motile microgametes, which are expelled in a process called exflagellation. Surprisingly little is known about the actors involved in thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 73 publications
5
24
0
Order By: Relevance
“…Δ kinesin-8B parasites produced no male gametes as shown previously (Depoix et al, 2020;Zeeshan et al, 2019a), while there was a significant decrease in male gamete formation in Δ kinesin-15 parasites (Fig. 4B).…”
supporting
confidence: 78%
“…Δ kinesin-8B parasites produced no male gametes as shown previously (Depoix et al, 2020;Zeeshan et al, 2019a), while there was a significant decrease in male gamete formation in Δ kinesin-15 parasites (Fig. 4B).…”
supporting
confidence: 78%
“…The mitogen‐activated protein kinase 2 (MAP‐2) affects the final stages of male gamete formation in both P. berghei and P. falciparum (Hitz, Balestra, Brochet, & Voss, 2020; Tewari, Dorin, Moon, Doerig, & Billker, 2005). Recent studies have revealed the participation of some structural and motor proteins in axoneme assembly (Depoix et al, 2020; Marques et al, 2015). Later in male gametogenesis, the egress process requires the release of lytic factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Kinesin-8s are among the most widely distributed kinesin subfamilies across eukaryotes 8 , perhaps because of their functional adaptability to both move processively along MTs and to influence MT dynamics. To understand the molecular basis of P. berghei kinesin-8B function in parasite transmission 6,7 , we characterised its motor domain and compared it with kinesin-8B from P. falciparum . Our biochemical and structural data provide evidence of conserved and precisely tuned mechanochemistry in these motors, which is distinct compared to other kinesin-8s characterised to date, including those in the parasite’s mammalian hosts.…”
Section: Discussionmentioning
confidence: 99%
“…A conserved role for catalytic depolymerases in male gamete formation Plasmodium kinesin-8Bs are expressed exclusively in male gametocytes, the only flagellated stage of the parasite life cycle. While deletion of the P. berghei kinesin-8B has no effect on parasite blood stages 42 and also has no effect on genome duplication during male gametogenesis, kinesin-8B knockout parasites exhibit disrupted flagella assembly and parasite transmission is blocked 6,7 . The motor domains from P. berghei and P. falciparum kinesin-8Bs exhibit very similar properties in vitro which, together with their very similar expression profiles 43 , suggest a conserved function for kinesin-8Bs across Plasmodium species.…”
Section: Plasmodium Kinesin-8bs Share Some Structural Features With K...mentioning
confidence: 99%
See 1 more Smart Citation